Family Business in Gulf Cooperation Council Countries - Ramadani, Veland; Aloulou, Wassim J.; Zainal, Mohammad (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume represents a comprehensive state-of-the-art picture of family business and entrepreneurship issues in countries belonging to the Gulf Cooperation Council. It provides major theoretical and empirical evidence which depicts the current processes in each GCC country including problems, faced by family business owners and entrepreneurs, such as succession, financial constraints, and conflicts. The chapters offer recommendations to policy makers on how to improve the general business environment and encourage potential investors, researchers, academicians, and professionals to be more involved in the region. The book is an outcome of a long-lasting endeavor and includes contributions from highly reputed authors and experts from the region and abroad.
Family business in Gulf Cooperation Council Countries: Introductory aspects -- Family business in Bahrain -- Family business in Kuwait -- Family business in Qatar -- Family business in Oman -- Family business in Saudi Arabia -- Family business in the United Arab Emirates -- Family business in Gulf Cooperation Council Countries: Towards the future. .
Keywords: Family-owned business enterprises; Regional economics; Spatial economics; Economic history; Family Business; Regional and Spatial Economics; Economy-wide Country Studies